Business Model Canvas Innovation at Luki Mas Fish Business in Bandung City - Setiawan, Martin; Kania, Trisa Nur (Journal of Economic Empowerment Strategy (JEES), 2024)
LUKI MAS is a business engaged in fisheries located at Jalan Pasir Impun Bandung. Based on research in the field, researchers raised problems in company activities that have not succeeded in the business model used by LUKI MAS. The purpose of the research conducted was to provide the right strategy and business model to LUKI MAS based on the Business Model Canvas, Know the Business Model Canvas applied to LUKI MAS and know the right business model design for LUKI MAS. The research method used is a descriptive qualitative method. Primary data collection techniques use source triangulation through participatory observation, structured interviews, audio and visual materials, while secondary data collection is carried out by literature studies. Data analysis techniques use the Miles and Huberman model through the process of data collection, data reduction, data presentation and conclusions. Based on the data obtained from the results of the study, that the description of the LUKI MAS business model using the Business Model Canvas in general can be said to be quite good and based on the results of the evaluation using SWOT analysis produces recommendations for new business strategies, the business model that is currently running is able to meet the nine elements of the Business Model Canvas Building blocks. The results of the Business Model Canvas Analysis on the LUKI MAS customer segments have target customers from children to adults.